If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 9 = 39 + 2x Reorder the terms: 9 + 8x = 39 + 2x Solving 9 + 8x = 39 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + 8x + -2x = 39 + 2x + -2x Combine like terms: 8x + -2x = 6x 9 + 6x = 39 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + 6x = 39 + 0 9 + 6x = 39 Add '-9' to each side of the equation. 9 + -9 + 6x = 39 + -9 Combine like terms: 9 + -9 = 0 0 + 6x = 39 + -9 6x = 39 + -9 Combine like terms: 39 + -9 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 4(d-2.5)=10 | | 8-5(3-2x)=30 | | 2e+6-5e=-12 | | (-2x+1)(2x+1)-3=0 | | g=5ah | | -7+v=8 | | b+12=10 | | 7x+5=6+2x | | 14x-16=64-2x | | 5*5-11+9= | | 8x-10=974 | | 6x+33=741 | | 7x+5=768 | | 5a-45= | | 3x+2y=4y-3x | | (x+5)(x-2)+3(x+1)=0 | | 4h^2+6h-133=0 | | 3a+7a-a= | | 9=-2r+2 | | x:(x+1)+6(x+3)=4 | | a+6b-2c+4a-4b+5c= | | 6x+23=16x-23 | | 6x+23=16x+57 | | 4/3r-3=r+2/3-1/3r | | 2f-5g-6f-2g+4f+8g= | | -5+x/3=9 | | 3.5=12s-58 | | -18+x^2-10y-y^2=0 | | x^2=y^2+10y+18 | | 2x+5y+3= | | 1+2x=x-17 | | 5a-2+8a+7-6a-3= |